Trade Dispute Adjudication and Trade Unions' Satisfaction of Justice Served in the Nigerian Oil and Gas Industry - Ikeije, Ugochukwu .U.; Nwakanma, Chinegbonkpa H. A.; Johnpedro, Mary .I. (Journal of Technology Management and Business, 2021)
This study examines the impact of trade dispute adjudication on the trade unions' satisfaction of justice served in the Nigerian oil and gas industry. This study employs a survey research design, involving the use of in-depth-interview of the officials of the major unions in the oil industry. The population was National Union of Petroleum and Natural Gas Workers (NUPENG) and Petroleum and Natural Gas Senior Staff Association of Nigeria (PENGASSAN) officials. The sample was drawn from the trade union officials of five selected oil and gas companies in Nigeria using purposive and stratified random sampling techniques. The purposive sampling technique was used in selecting the secretaries of the unions, whereas stratified random sampling technique was used in electing other officials. Fourteen (14) officials were drawn from NUPENG and sixteen (16) officials were drawn from (PENGASSAN) for the purpose of the interview. The study found that not less than 74% of the trade unions' officials are not very satisfied with the justice served by the National Industrial Court as they reported that the process of adjudicating trade disputes in the oil and gas industry is frustrating, costly and time-consuming. Based on this finding, it was recommended that the Government should enhance the level of satisfaction of the trade unions with the justice served by the National Industrial Court by avoiding unnecessary interference with the processes of adjudication and making the process faster and less expensive in delivering judgement.